Comparative Utilization of Reverse and Anatomic Total Shoulder Arthroplasty: A Comprehensive Analysis of a High-volume Center. Issue 24 (15th December 2018) - Chalmers, Peter N.; Salazar, Dane H.; Romeo, Anthony A.; Keener, Jay D.; Yamaguchi, Ken; Chamberlain, Aaron M.
Abstract : Introduction: The purpose of this study was to determine how reverse and total shoulder arthroplasty (RTSA and TSA) comparative utilization, postoperative diagnoses, demographics, and perioperative data have changed between 2005 and 2015. Methods: This was a single-center retrospective review of all primary TSAs and RTSAs. Results: Our cohort included 1, 192 RTSAs and 1, 600 TSAs. Although both RTSA and TSA volume increased, RTSA increased from 27% to 52% of shoulder arthroplasty. The number of RTSAs performed for osteoarthritis and irreparable rotator cuff tears increased, and the proportion of RTSAs performed for rotator cuff tear arthropathy decreased. The mean age decreased for RTSA and TSA, and American Society of Anesthesiologists scores increased for both. Discussion: Over the past decade, RTSA has become the most common primary shoulder arthroplasty, reflecting the clinical success of the procedure. This increase is due to both an increase in the number of RTSAs performed for rotator cuff tear arthropathy as well as expanding surgical indications for RTSA. Level of Evidence: Retrospective, level IV